Burning through the pain: treatments for diabetic neuropathy. Issue 12 (10th September 2015) - Javed, S.; Alam, U.; Malik, R. A.
Abstract : The rise in the global burden of diabetes is spurring an increase in the prevalence of its complications. Diabetic peripheral neuropathy (DPN) is a common and devastating complication of diabetes, with multiple clinical manifestations. The most common is a symmetrical length‐dependent dysfunction and damage of peripheral nerves. The management of DPN rests on three tenets: intensive glycaemic control, even though the evidence of benefit is questionable in people with type 2 diabetes; pathogenetic therapies; and symptomatic treatment. A number of pathogenetic treatments have been evaluated in phase III clinical trials, including α‐lipoic acid (stems reactive oxygen species formation), benfotiamine (prevents vascular damage) and aldose‐reductase inhibitors (reduce flux through the polyol pathway), protein kinase C inhibitors (prevent hyperglycaemia‐induced activation of protein kinase C), nerve growth factors (stimulate nerve regeneration) and Actovegin® (improves tissue glucose and oxygen uptake). However, none have gained US Food and Drug Administration or European Medicines Agency (EMA) approval, questioning the validity of current trial designs and the endpoints deployed to define efficacy. For painful diabetic neuropathy, clinical guidelines recommend: atypical analgesics for pain relief, including duloxetine and amitriptyline; the γ‐aminobutyric acid analogues gabapentin and pregabalin; opioids, including Tapentadol; and topical agents such as lidocaine and capsaicin. No single effective treatment exists for painful DPN, highlighting a growing need for studies to evaluate more potent and targeted drugs, as well as combinations. A number of novel potential candidates, including erythropoietin analogues and angiotensin II type 2 receptor anatagonists are currently being evaluated in phase II clinical trials.